2001
DOI: 10.1080/00039890109604470
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Diarrhea in Children Living in Areas with High Levels of Nitrate in Drinking Water

Abstract: Given that there was documented evidence of an association between diarrhea and high nitrate ingestion, the authors examined drinking water nitrate concentration and its possible correlation(s) with methemoglobin levels, cytochrome b5 reductase activity, and recurrent diarrhea. In addition, the authors studied histopathological changes in the intestines of rabbits in an animal model. Five village areas were studied, and nitrate concentrations (expressed in mg of nitrate per liter of water) of 26, 45, 95, 220, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In developing countries including Nigeria, there are confirmations that harmful chemicals and microorganisms from unsanitary dumpsites are introduced into adjacent surface and ground waters used as drinking water by communities [28,29]. Epidemiological data from consumption of unsafe water showed increased risk of nephrotoxicity, cancer and central nervous system defects [30,31]. Exposure to chemicals through drinking contaminated water is capable of inducing DNA damage and enhancing genetic changes in somatic cells that can result in decreased cell survival or transformation and eventual reproductive abnormalities and cancer formation in organisms [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…In developing countries including Nigeria, there are confirmations that harmful chemicals and microorganisms from unsanitary dumpsites are introduced into adjacent surface and ground waters used as drinking water by communities [28,29]. Epidemiological data from consumption of unsafe water showed increased risk of nephrotoxicity, cancer and central nervous system defects [30,31]. Exposure to chemicals through drinking contaminated water is capable of inducing DNA damage and enhancing genetic changes in somatic cells that can result in decreased cell survival or transformation and eventual reproductive abnormalities and cancer formation in organisms [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…This water, in rural zones is used as drinking water and thus their pollution by nitrates could represent a threat for human health. In this subject, many studies showed the existence of relation between the consumption of nitrates in the water and the appearance of certain diseases such as: methemoglobinemia (Fan and Steinberg, 1996), goitre (Gatseva et al, 1998;Vladeva et al, 2000), gastric cancer (Gilli et al, 1984;MoralesSuarez-Varela et al, 1995) as well as respiratory (Gupta et al, 2000) and digestive (Gupta et al, 2001) complications. These effects, for the majority, were induced with nitrate amounts in water exceeding the standard set by WHO, i.e 50 mg/l (1998).…”
Section: Introductionmentioning
confidence: 97%
“…Nitrate and phosphate pollution of surface water is of high concern as it may have negative impacts on water supply and ecosystems. High nitrate concentrations in water serving as a source for drinking water is a serious health problem, being known for many years as the cause of blue baby syndrome (Comly 1945;Gelberg et al 1999) and related to increased levels of diarrhoea of children (Gupta 2001).…”
Section: Introductionmentioning
confidence: 99%